Engineered Cell Elongation Promotes Extracellular Electron Transfer of Shewanella Oneidensis - Feng Li; Huan Yu; Baocai Zhang; Chaoning Hu; Fei Lan; Yuxuan Wang; Zixuan You; Qijing Liu; Rui Tang; Junqi Zhang; Chao Li; Liang Shi; et al. (Advanced Science, 2024)
Abstract To investigate how cell elongation impacts extracellular electron transfer (EET) of electroactive microorganisms (EAMs), the division of model EAM Shewanella oneidensis (S. oneidensis) MR‐1 is engineered by reducing the formation of cell divisome. Specially, by blocking the translation of division proteins via anti‐sense RNAs or expressing division inhibitors, the cellular length and output power density are all increased. Electrophysiological and transcriptomic results synergistically reveal that the programmed cell elongation reinforces EET by enhancing NADH oxidation, inner‐membrane quinone pool, and abundance of c‐type cytochromes. Moreover, cell elongation enhances hydrophobicity due to decreased cell‐surface polysaccharide, thus facilitates the initial surface adhesion stage during biofilm formation. The output current and power density all increase in positive correction with cellular length. However, inhibition of cell division reduces cell growth, which is then restored by quorum sensing‐based dynamic regulation of cell growth and elongation phases. The QS‐regulated elongated strain thus enables a cell length of 143.6 ± 40.3 µm (72.6‐fold of that of S. oneidensis MR‐1), which results in an output power density of 248.0 ± 10.6 mW m−2 (3.41‐fold of that of S. oneidensis MR‐1) and exhibits superior potential for pollutant treatment. Engineering cellular length paves an innovate avenue for enhancing the EET of EAMs.